Cultural Heritage and the governance of the UNESCO sites of Campania - Barbara Martini (European Regional Science Association (ERSA), 2011)
The 'good tourism' is capable of generating development in terms of cohesion and sustainability in the territory where it is located. The literature for a long period, has considered the good tourisms in the same way as all other goods. The aim of this study is to demonstrate that by using a different definition of 'good tourism', Cultural Heritage, and appropriate mechanisms for management of the 'Great Cultural Attractions', territorial governance, it is possible to exploit the full potential of the asset. The territorial governance model proposed is bottom-up which includes the participation of all stakeholders in the area will be applied to the Campania Region which has five UNESCO sites. This approach should be able to create a virtuous cycle of growth in the region.
Keywords: 330